The Adaptation of Shan Youth Through Education in Thailand - Nasee, Pisith (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2023)
This article aims to present the results of the research entitled “The adaptation of Shan youth through education in Thailand.” The research objectives are to examine the factors and conditions of entry of second-generation Shan migrants who have enrolled into the Thai educational system, and their adaptation within this process. The study applied a qualitative research method, in which data was collected between May 2020 and January 2021 from four main case studies concerning those who are studying in/graduating from vocational and/or higher educational institutions in Chiang Mai. The study employed the concepts of Segmented Assimilation and Community Cultural Wealth. The main findings are that there are two key factors that have facilitated the entry of second-generation Shan migrants into education, in particular vocational and higher education. The first concerns the structural conditions of the educational system, which have gone through considerable revisions since the 1980s in order to improve access to education for disadvantaged children. The second factor concerns the individual level, in which case it was found that ‘spaces of hope’ are created throughout the educational process. However, the adaptation strategies that are taken up are flexible. Additionally, they apply various forms of capital which develop within the family and migrant community contexts. Analysis through an asset-based approach assists us to realize the multiple strengths of second-generation Shan migrants in their adaptation and persistence until graduation under various constraints in Thai society.